Implementation of the Numbered Heads Together Learning Model Assisted by Image Media to Improve the Activities and Learning Outcomes of Science Students of Grade VI of SD Negeri 10 Koto - David Fernanda; Ismira Ismira; Siti Aisyah (FKIP - Universitas Riau, 2026)
This study was motivated by the low level of student activity and learning outcomes in science learning. The study aimed to improve the learning activities and science learning outcomes of sixth-grade students at SD Negeri 10 Koto through the implementation of the Numbered Heads Together (NHT) learning model assisted by visual media. This research used classroom action research conducted in two cycles. The subjects of this study were 26 sixth-grade students. Data were collected through observation of student learning activities and tests of learning outcomes at the end of each cycle. The results showed that student learning activities increased from 63.46% in cycle I to 82.69% in cycle II. In addition, student learning outcomes also improved from 65.38% in cycle I to 80.77% in cycle II. These findings indicate that the implementation of the Numbered Heads Together learning model assisted by visual media can improve students’ learning activities and science learning outcomes. Based on the results of the study, it can be concluded that the implementation of the Numbered Heads Together learning model assisted by image media can improve students’ learning activities and science learning outcomes.